ANALISIS PENGARUH PENERAPAN GREEN ACCOUNTING TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sulistiawati, Eka; Dirgantari, Novita (Universitas Muhammadiyah Malang)
The research was qualitative research aimed to find out the effect of green accounting application toward profitability. The independent variables in this research were environmental performance and environmental disclosure, while the dependent variable was profitability. The research objects were the mining companies registered in Indonesia Stock Exchange within 2013-2015 period. This research used 54 samples. The sampling technique was purposive sampling,while the data analysis techniques were descriptive statistic, classic assumption test, multipleregression analysis, and hypothesis test with significance level (Ã¡) of 0,05. The research resultshowed that the environmental performance did not positively affect profitability with the significance value of 0,129 > 0,05 and the environmental disclosure did not positively affect profitability with the significance value of 0,715 > 0,05.Ke ywords: environmental disclosure, green accounting, environmental performance, profitability.